2020
DOI: 10.3390/w12051258
|View full text |Cite
|
Sign up to set email alerts
|

Application of Composite Pre-Polymerized Coagulants for the Treatment of High-Strength Industrial Wastewaters

Abstract: The aim of this study was the investigation of alternative pre-polymerized coagulants for the treatment of high-strength industrial wastewaters, such as those created by tanneries, or by yeast production industries. The novel inorganic composite coagulant examined in this study (as well as variations of it) was denoted as PSiFAC1.5-10-15. The contribution of a typical polyelectrolyte to improve the effectiveness of the coagulation/flocculation (C/F) process was additionally studied, either by adding it separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 40 publications
0
10
0
3
Order By: Relevance
“…Tannery wastewater is the product of a transformation process from organic matter to non-degradable matter, which requires the addition of compounds and additives that allow such transformation, generating in turn waste highly polluting not only for human health, but also for the environment [ 34 ]. These wastewaters have as main characteristics a dark brown color, a characteristic odor due to the presence of volatile organic compounds, organic and inorganic carbon, phosphorus (P), nitrogen compounds (N) [ 9 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], fats and other highly polluting compounds at certain concentrations, such as chemical oxygen demand (COD), biological oxygen demand (BOD), total dissolved solids (TDS), chlorides, sulfates and heavy metals such as Zinc (Zn) and chromium (Cr), among other things [ 37 , 43 , 44 , 45 , 46 ]. Goswami and Mazumder [ 47 ] reported a typical characterization of tannery wastewater, where COD concentrations were observed between 500 and 11,500 mg*L −1 , total Kjeldahl nitrogen (TKN)—200–550 mg*L −1 , observing that the highest fraction is available as ammonia nitrogen (NH 3 –N), total chromium concentrations (Cr(VI) and Cr(III)) in a range of 5–140 mg*L −1 , slow biodegradability due to the content of biodegradable compounds is less than 50% and very high total dissolved solids (TDS) compared to total suspended solids (TSS).…”
Section: Pollutant Loads From Tannery Wastewatersmentioning
confidence: 99%
See 1 more Smart Citation
“…Tannery wastewater is the product of a transformation process from organic matter to non-degradable matter, which requires the addition of compounds and additives that allow such transformation, generating in turn waste highly polluting not only for human health, but also for the environment [ 34 ]. These wastewaters have as main characteristics a dark brown color, a characteristic odor due to the presence of volatile organic compounds, organic and inorganic carbon, phosphorus (P), nitrogen compounds (N) [ 9 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], fats and other highly polluting compounds at certain concentrations, such as chemical oxygen demand (COD), biological oxygen demand (BOD), total dissolved solids (TDS), chlorides, sulfates and heavy metals such as Zinc (Zn) and chromium (Cr), among other things [ 37 , 43 , 44 , 45 , 46 ]. Goswami and Mazumder [ 47 ] reported a typical characterization of tannery wastewater, where COD concentrations were observed between 500 and 11,500 mg*L −1 , total Kjeldahl nitrogen (TKN)—200–550 mg*L −1 , observing that the highest fraction is available as ammonia nitrogen (NH 3 –N), total chromium concentrations (Cr(VI) and Cr(III)) in a range of 5–140 mg*L −1 , slow biodegradability due to the content of biodegradable compounds is less than 50% and very high total dissolved solids (TDS) compared to total suspended solids (TSS).…”
Section: Pollutant Loads From Tannery Wastewatersmentioning
confidence: 99%
“…Goswami and Mazumder [ 47 ] reported a typical characterization of tannery wastewater, where COD concentrations were observed between 500 and 11,500 mg*L −1 , total Kjeldahl nitrogen (TKN)—200–550 mg*L −1 , observing that the highest fraction is available as ammonia nitrogen (NH 3 –N), total chromium concentrations (Cr(VI) and Cr(III)) in a range of 5–140 mg*L −1 , slow biodegradability due to the content of biodegradable compounds is less than 50% and very high total dissolved solids (TDS) compared to total suspended solids (TSS). Different studies have reported high values of BOD, COD and even the presence of Cr in effluents [ 13 , 36 , 39 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Other compounds have been reported in these wastewaters, finding results of acidic pH between 3.4 ± 0.0351 and 5.96 ± 0.0351 [ 56 , 57 , 58 ] and basic pH between 8.0 ± 0.4 and 11.64 ± 0.53 [ 37 , 41 , 46 , 51 , 52 , 54 , 55 , 59 , 60 , 61 ]; in relation to TDS, typical values can have concentrations ranging from 2355 ± 85 mg*L −1 to 10,000 ± 800 mg*L −1 [ 9 , 37 , 39 , 42 , 61 , 62 ]; high concentrations have been recorded that can be between 10,560 ± 78 mg*L −1 and 72,400 ± 0.10 mg*L −1 [ 35 , 40 , 53 , 54 , 55 , 63 ]; as for BOD, the average values can be in low ranges from 160 ± 15.8 mg*L −1 to 1250 ± 38 mg*L −1 [ 37 , 39 ,…”
Section: Pollutant Loads From Tannery Wastewatersmentioning
confidence: 99%
“…13 κατά την ανάλυση με XRD είναι η εμφάνιση σχετικά έντονων κορυφών σε μικρές γωνίες (5-35 ο 2θ), ενώ ο χημικός τύπος με τον οποίο ταυτοποιήθηκε ήταν ο εξής…”
unclassified
“…[10][11][12][13][14][15] , τόσο για την απομάκρυνση της θολότητας, όσο και της απορρόφησης στα UV 254nm , με δόση του κροκιδωτικού 2 mg Al/L. Στη συνέχεια, μελετήθηκε η αποτελεσματικότητα των κροκιδωτικών υλικών με την προσθήκη πολυηλεκτρολύτη (ΑPE) ως πρόσθετο στη δομή του κροκιδωτικού, εναλλακτικά της προσθήκης του πολυπυριτικού οξέος (pSi).…”
unclassified
See 1 more Smart Citation